Pelaksanaan Penghapusan Perdagangan Perempuan dan Anak Di Kabupaten Bintan - Elza Syarief; Ibnu Kholdun (Journal of Law and Policy Transformation, 2020)
The thesis discussed the effectiveness of task force of the efforts to the removal of trade women and boy who is victims of human . Various policies which created a government pertaining to crimes trade women and children , basically the policy made relatively comprehensive , starting from the constitution of 1945 to regulations below. Effort task force against the removal of trade women and children is currently still less effective. This can be seen from there are still many the cases of trafficking of women and children. Efforts task force made in to reduce and a handle human trafficking as a form of prevention to be victims , done by means of coordination , socialization , rehabilitation and reintegrated.